(untitled) (Baghdad Science Journal, 2024)
The goal of this research is to develop a unique cryptographic method that makes use of Aboodh and its inverse transform in combination with the S-Box approach. The results of evaluations indicate that this work is appropriate for use in safe cryptographic applications, and it provides clues regarding the building of an image cryptosystem based on the complicated behaviors that it demonstrates. After applying the methodologies that have been provided to depict data taken from real-life situations, the results have been evaluated using a wide variety of statistical and performance criteria. The ﬁndings of this investigation result in an improvement to the reliability of the cryptosystem.